Prognostic value of kappa free light chain index in patients with primary progressive multiple sclerosis - Schmidauer, Martin; Berek, Klaus; Auer, Michael; Bsteh, Gabriel; Cavalla, Paola; Di Pauli, Franziska; Di Filippo, Massimiliano; Deisenhammer, Florian; Emeršič, Andreja; Föttinger, Fabian; Gaetani, Lorenzo; Hassler, Michaela; et al. (Frontiers in Immunology, 2025)
BackgroundThe kappa free light chain (κ-FLC) index is a well-established biomarker in multiple sclerosis (MS). While the prognostic value of the κ-FLC index has been demonstrated in early relapsing–remitting MS, its prognostic value in primary progressive MS (PPMS) has not yet been investigated.MethodsIn this multicenter, retrospective cohort study, patients diagnosed with PPMS with diagnostic lumbar puncture and clinical follow-up of at least 12 months were recruited from nine MS centers across five countries. At baseline, age, sex, disease duration, and the number of T2 hyperintense (T2L) and contrast-enhancing T1 lesions (CEL) on MRI were determined. κ-FLC was measured using nephelometry/turbidimetry, and the κ-FLC index was calculated as (CSF κ-FLC/serum κ-FLC)/albumin quotient. At follow-up, the occurrence of disability progression and the administration of disease-modifying treatment (DMT) were registered. The primary endpoint was time to disability progression.ResultsA total of 121 PPMS patients were included with a median age of 53 years (25th–75th percentile: 46–59) and a balanced sex distribution (48.8% female). Multivariable Cox regression analysis revealed no significant association between the κ-FLC index and disability progression [hazard ratio (HR) 1.0, p = 0.950]. Prior use of DMT (HR 0.60, p = 0.023) and brain T2L > 9 at baseline (HR 2.22, p = 0.026) were significantly associated with disability progression. The remaining covariates, including age, sex, disease duration, and CEL, showed no significant associations.ConclusionThe κ-FLC index does not predict disability progression in PPMS, contrasting its growing role as a prognostic biomarker in relapsing MS. This highlights phenotypic differences in MS pathophysiology and underscores the need for prognostic biomarkers in PPMS.